Review PaperAlclometasone dipropionate: properties and clinical uses - Kisiel, Katarzyna; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Topical glucocorticosteroids are the mainstay of therapy in inflammatory skin disorders. The therapeutic effect of glucocorticosteroids depend on their chemical structure, physio-chemical properties, concentration of the active substance, pharmaceutical form, and affinity for specific receptors. Alclometasone dipropionate is a new-generation non-fluorinated topical glucocorticosteroid used in the treatment of inflammatory glucocorticosteroid responsive skin disorders (i.e. atopic dermatitis, contact dermatitis, psoriasis vulgaris, lichen planus) in adults and in pediatric patients older than 1 year of age. The unique properties of the compound result from the presence of a chlorine atom in position 7 which increases the potency of its effect without increasing the incidence of local and systemic adverse effects. Apart from its characteristic properties of glucocorticosteroids as a class (it is anti-inflammatory, antiproliferative, immunosuppressant and vasoconstrictive) the preparation has a beneficial effect on skin hydration which makes alclometasone the glucocorticosteroid of choice in dermatoses associated with pruritus and excessive skin dryness. Adverse reactions to alclometasone are rare and usually mild and transient. Alclometasone dipropionate is available in two formulations, i.e. 0.05% cream and 0.05% ointment.